2001
DOI: 10.1007/s005200000165
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in disease-free cancer patients compared with fatigue in patients with Chronic Fatigue Syndrome

Abstract: The goal of our work was to assess fatigue in disease-free cancer patients with help of a validated fatigue questionnaire. Furthermore, we wished to analyse the relationship between severe fatigue and former treatment modalities, problems of concentration and motivation, physical activity, functional impairment, depression and anxiety and finally, to compare severely fatigued disease-free cancer patients and patients with Chronic Fatigue Syndrome (CFS). The participants were 85 adult cancer patients and 16 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
4
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 18 publications
4
107
4
5
Order By: Relevance
“…These results are comparable to the extent of problems experienced by patients with chronic fatigue syndrome. However, compared to severely fatigue disease-free cancer patients, the LGG patients in our study report more problems with concentration [6].…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…These results are comparable to the extent of problems experienced by patients with chronic fatigue syndrome. However, compared to severely fatigue disease-free cancer patients, the LGG patients in our study report more problems with concentration [6].…”
Section: Discussioncontrasting
confidence: 53%
“…In contrast, LGG patients are considered to be never completely free of disease [5]. As a consequence, being confronted with a life-threatening illness can lead to feelings of depression and anxiety for the future, which both may be correlated with fatigue [6,[22][23][24][25][26][27]. Furthermore, LGG patients have specific cognitive problems [5], which presumably may also be related to fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also indicated strong relationships between anxiety and depression and CRF in cancer survivors (34,(38)(39)(40)42,(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) two reported that married individuals had higher fatigue than those who were not married (96,97). A relationship has also been reported between age and fatigue in cancer survivors (34,39,41,83,93,(96)(97)(98).…”
Section: Fatigue After Anti-cancer Treatmentmentioning
confidence: 90%
“…A score of 34 or higher on the eight-item subscale for subjective fatigue has often been used as a cut-off point for severe fatigue. 9,10 Both of the study's outcome definitions were based on multiple outcome measurements during follow-up. Recovery was defined as a score <34 on the severity scale of the CIS at 4, 8, and 12 months after baseline.…”
Section: Definition Of Outcomementioning
confidence: 99%